Public science policy and administration - Rosenthal, Albert H. (Albuquerque: University of New Mexico Press, 1973)
In this book eleven national authorities of varied background in science, education, and government administration contribute their experience and their judgment in an effort to deal with the major aspects of the subject.
Keywords: Public science policy